Toxic Shock Syndromes - Laupland, K. B. (Infectious Diseases in Critical Care, 2010)
Staphylococcal toxic shock syndrome (TSS) was first described in seven children aged 8–17 years by Todd et al. in 1978 [1]. It shortly thereafter became well known as an illness of menstruating women who used tampons [2, 3]. The syndrome is characterized by rapid onset of fever, hypotension, and multisystem failure with desquamating rash occurring in convalescence [4]. The majority of early cases reported were menstrually associated (MTSS) but this has been changing with an increasing proportion of cases non-menstrually associated (NMTSS) [5].